Regional Analysis of Gender Inequality in the Kazakh Labor Market in the Context of Sustainable Development - G. N. Nyussupova; G. B. Aidarkhanova; L. B. Kenespayeva; G. B. Aubakirova (Экономика: стратегия и практика, 2024)
Kazakhstan demonstrates its commitment to promoting gender equality and works closely with the global community. Over the past decade, the gender gap in the structure of the labor force of the Republic of Kazakhstan has narrowed slightly. However, gender gaps persist. Women in Kazakhstan make up slightly more than half of the country’s total population. Still, their contribution to the republic’s economic performance, growth, and well-being is significantly below its potential. Access to the Republic’s gender statistics is essential and critical for studying and tracking changes in gender inequality. This article examines the gender dynamics of the labor market of the Republic of Kazakhstan at the macro and micro levels using a geographic information system (GIS). GIS tools provide display and analysis capabilities that are underutilized in workforce development, monitoring, and management. In this study, the authors tried to model spatial indicators of gender inequality in the labor market of the Republic of Kazakhstan. The study results show that the employment rate and the level of women’s wages are primarily related to the gender segregation of vocational education, which lays the foundation for sectoral differentiation of employment with different geographical distributions. The greater competitiveness of women in the labor market of Kazakhstan is also hampered by the so-called “glass ceiling” or low accessibility to leadership positions. The wage gap between men and women in the republic has remained unchanged for a long time and shows no signs of reduction. In addition, such an important element of the labor market as unpaid domestic work, which is carried out mainly by women, remains unrecognized.